Need Analysis on Implementing Multilingualism in High School - Atibrata, Tyas Gita; Margana, Margana; Herda, Rozanah Katrina; Saputro, Eko Prasetyo Nugroho (Journal of English Language and Education, 2024)
This study investigated the needs of high school students in Yogyakarta regarding multilingualism-based English language learning. A quantitative research design was employed, involving a questionnaire survey of 1215 students. Data analysis revealed that students expressed a strong preference for a multilingual approach, highlighting the need for integrating Indonesian and/or local languages into English language instruction. Students perceived that this approach could alleviate language anxiety, enhance motivation, and improve both receptive and productive language skills. These findings align with previous research, which suggests that multilingualism can create more inclusive and effective learning environments. The study underscores the importance of incorporating diverse linguistic resources to optimize English language learning outcomes.